Statistical description of noise propagation in a built-up area - E. WALERIAN; R. JANCZUR (Archives of Acoustics)
The paper presents three diffusion models of sound propagation through a space with obstacles proposed by Kurze, Kuttruff and Yeow. The models contain simple expressions for the sound attenuation what makes them attractive to use. Here, the models are applied to a segment of a built-up area. Considerable differences appearing between the values of the sound excess attenuation confirm the fact that the diffuse model can be used only as a tool for very rough field investigation. One has to be very careful while interpreting the results obtained, bearing in mind all the limitations of the models applied and the vague way of estimation of the model parameters.